2017
DOI: 10.1177/2058460117717765
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy computed tomography angiography: virtual calcified plaque subtraction in a vascular phantom

Abstract: BackgroundMaterial decomposition of dual-energy computed tomography (DECT) enables subtraction of calcified plaque.PurposeTo evaluate the accuracy of lumen area measurement in calcified plaque by subtraction of DECT and to determine the effect of contrast material concentration, lumen diameter, density, and thickness of calcified plaque for the measurement.Material and MethodsVessel phantoms were made with six lumen diameters (5.7, 4.9, 3.9, 3.0, 1.9, and 1.3 mm) and six types of calcified plaques with three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The focus of the study was on testing an advanced spectral algorithm under the increasingly difficult situation generated by the phantom motion toward higher heart rates. Existing literature in this context is often limited to a static evaluation or a simple spectral postprocessing 22,23 …”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of the study was on testing an advanced spectral algorithm under the increasingly difficult situation generated by the phantom motion toward higher heart rates. Existing literature in this context is often limited to a static evaluation or a simple spectral postprocessing 22,23 …”
Section: Highlightsmentioning
confidence: 99%
“…Existing literature in this context is often limited to a static evaluation or a simple spectral postprocessing. 22 , 23 …”
Section: Highlightsmentioning
confidence: 99%
“…Analogously, another research group [ 52 ] fabricated vascular phantoms to evaluate the accuracy of lumen area measurement using a modified dual-energy CT protocol. They investigated the effects of contrast material concentration, vessel diameter (5.7, 4.9, 3.9, 3.0, 1.9, and 1.3 mm), and thickness of calcified plaque (2.0 vs. 4.0 mm) on this measurement.…”
Section: Applications Of Biomimetic Vascular Models For Atherosclerosismentioning
confidence: 99%
“…The results indicated that extensively calcified plaques lead to an underestimated measurement of the lumen area, meaning a false diagnosis of vascular stenosis; likewise, this underestimation was as low as the vessel diameter was large. Subsequently, through preventing in vivo experimentation, this study proved that further investigation must be conducted before implementing these protocols in clinical practice [ 52 ].…”
Section: Applications Of Biomimetic Vascular Models For Atherosclerosismentioning
confidence: 99%
“…The latter is not unique to one specific type of tissue but related to the atomic composition of the tissue. CT scanning with spectral energy, with simultaneous acquisition of datasets using two x-ray spectra of diverse energies, allows optimisation of contrast in vascular imaging, but also virtual subtraction of bone structures, calcified areas or iodine in contrast-enhanced images [1][2][3][4]. Manufacturers provide diverse technologies for acquiring spectral CT data that can potentially give different results.…”
Section: Introductionmentioning
confidence: 99%